Treatment of Gram-negative bacterial infections by potentiation of antibiotics. (October 2016) - Zabawa, Thomas P; Pucci, Michael J; Parr, Thomas R; Lister, Troy
Graphical abstract: Highlights: Potentiating molecules permeabilize the outer membrane of Gram-negative bacteria. Agents that previously acted only on Gram-positive organisms, can now treat Gram-negative infections. Potentiator molecules include polymyxin, cationic steroid, and olig-acyl-lysyl derivatives. Abstract : Infections caused by antibiotic-resistant pathogens, particularly Gram-negative bacteria, represent significant treatment challenges for physicians resulting in high rates of morbidity and mortality. The outer membrane of Gram-negative bacteria acts as a permeability barrier to many compounds that would otherwise be effective antibacterial agents, including those effective against Gram-positive pathogens. Potentiator molecules disrupt this barrier allowing entry of otherwise impermeant molecules, thus providing a strategy to render multi-drug resistant pathogens susceptible to a broader range of antibiotics. Potentiator molecules are cationic and the mechanism of disruption involves interaction with the negatively charged outer membrane. This physical attribute, along with an often high degree of lipophilicity typically endears these molecules with unacceptable toxicity. Presented herein are examples of advanced potentiator molecules being evaluated for use in combination therapy for the treatment of resistant Gram-negative infections.